(untitled) (Palíndromo, 2022)
Every day it proves more than necessary studies on curriculum organizations, directed in na open and purposeful perspective concerned in the formation of independent and critical/reflective art teachers. This study ( Doctorate degree) dialogue through a bibliographic review – the production of Theses, Articles and Dissertations that rese[1]arch the training of this professional in the área of education in the face of devaluation and trends that currently influence and prevail, in the field of Knowledge.The reflections based on Critical ando n the analysis of contentes helped me to understand the existing tensions that appear in few researches deposited on the subject.To understand that, in the face of voices that oppose na authoritarianism that are increasingly presente in the educational scene, it is essencial to explore and believe in the power of teaching the arts in basic education and in a training of visual arts teachers thinking – together with other áreas of knowledge- in Human Development.